(untitled) (Bangladesh Journal of Botany, 2020)
Evaluation of the seed storage protein electrophoretic profile among popular cultivars of date palm (Pheonix dactylifera) available in different regions of Balochistan, Pakistan was conducted. The genetic diversity of seed proteins of 12 cultivars were examined by electrophoresis. Twenty one protein bands with different mobility rates were identified within a molecular weight range of 11 to 351 KDa. The cultivar from Panjgur (Soorri) was well resolved on SDS-PAGE from the all other cultivars and gave the highest number of intense bands due to unique genetic build up. Genetic diversity among cultivars was evaluated by constructing the dendrogram for protein bands, which showed the cultivar (SP1) which is significantly different from all other cultivars on the basis of similarities in molecular weight of proteins.